PEMEROLEHAN KALIMAT BAHASA INDONESIA PADA ANAK USIA 5 TAHUN (STUDI KASUS MARTA OKTAVIANI) - Ta, Evita (Universitas Tanjungpura, 2025)
This research is the acquisition of Indonesian sentences in 5 year old children, case study of Marta Oktaviani, Syntax study. This research uses a descriptive method in the form of qualitative research. The data source for this research was obtained directly from the subject, a 5 year old child. The research data is the structure of Indonesian sentence patterns according to the chosen problem formulation. The data collection techniques used in this research were observation, interviews, TSLC, note taking, recording. The data collection tools used were observation sheets, gadgets and note-taking sheets. After that, the results of the analysis found that there were 16 declarative sentences, 9 interrogative sentences, 3 imperative sentences. From the results of the analysis obtained, children aged 5 years are more likely to use declarative sentences, because children aged 5 years understand more and are able to pronounce sentences quite well. Therefore, the role of parents is very important in the acquisition of sentences in children aged 5 years.